Criteria of Habitable Fishermen Settlements (Case Study of Fisherman Villages Sidoarjo) - Laili Maulidiyah; Dewi Septanti; Happy Ratna Santosa (IPTEK Journal of Proceedings Series, 2020)
The slums that occur in fishpond settlements are not only based on environmental conditions, but also based on people's perceptions about the slum standards themselves. Physically, fishing houses in coastal areas are larger than substandard materials, dense, coincide, make dirty, look more easy, settlements, fishermen, can be categorized as slums. The situation of this slum-looking settlement is the result of a very high increase in the flow of urbanization with the aim of survival and life in a place that needs more resources that can be used to sustain life. The method used for this study with the criteria for assessing fishermen settlements in the case study. The results of this study consist of factors that cause slums and slum free village criteria based on the conditions of fishermen settlements in the case study living in coastal fishermen settlements. Get results from studies that can help and become one that can be used for livable and slum-free assistance on topics that exist in fishing villages in Indonesia